Transient transfection using 222 nm far UV-C irradiation - Mane Nishimura; Yuki Shimizu; Tomohiro Fujii; Yu Okada; Takeshi Yamamoto; Yoshimasa Ogawa; Toru Koi; Yutaka Suehiro; Takahiro Yamasaki; Jun Nishikawa (Scientific Reports)
Abstract Ultraviolet (UV) light is never used for gene transfer because it damages DNA and harms cellular and plasmid DNA. A light source selectively radiating Far UV-C (F-UV) light causes less DNA damage. We investigated potential introduction of plasmids into cells by irradiating them with F-UV light. COS-7 and CHO-K1 cells were irradiated with 222 nm F-UV light. Then, DNA solution containing green fluorescent protein (EGFP) plasmid was added to the culture and incubated (37 °C, 5% CO2, 24 h) for fluorescence microscopy. Cytotoxicity of cells irradiated with the same energy as for gene transfer was evaluated. Characteristics of EGFP-positive cells were compared with non-transfected cells by propidium iodide (PI) and Hoechst staining. Cells with distinct green fluorescence were observed after F-UV light irradiation and addition of 200 ng of EGFP plasmid. COS-7 cells showed the highest number of EGFP-positive cells at 0.5 mJ/cm2 irradiation, whereas that for CHO-K1 cells was at 1 mJ/cm2 irradiation. Cytotoxicity was low in COS-7 at ≤ 1 mJ/cm2 irradiation and CHO-K1 at ≤ 0.5 mJ/cm2. Transfected cells did not incorporate PI, and their nuclei did not differ from those of non-transfected cells. We successfully transfected two cell lines with EGFP plasmids by F-UV irradiation.